Efektivitas Penilaian Anekdot untuk Mengukur Capaian Pembelajaran Kognitif Anak Usia Dini - Laksana, Dek Ngurah Laba; Maku, Karmelia Rosfinda Meo; Beo, Maria Aprinianti; Bue, Stefania Bibiana (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to evaluate the use of anecdotal assessment in measuring the cognitive learning achievement of early childhood children in the context of the Merdeka curriculum at the Integrated Early Childhood Education Citra Bakti. The method applied is qualitative descriptive with data collection techniques through interviews and documentation. Primary data sources include interview results and observations of children's and teachers' activities, while secondary sources consist of documented planning and assessments previously conducted. Data analysis was performed descriptively. The research findings indicate that at the Integrated Early Childhood Education Citra Bakti, the Merdeka curriculum is implemented using anecdotal assessment, covering achievements in religious values, morals, identity, and literacy. The effectiveness of anecdotal assessment is proven in evaluating the learning achievements of early childhood children in the Merdeka curriculum, providing a comprehensive overview of social, emotional, and cognitive development aspects. This approach is in line with the principles of the Merdeka curriculum, which focuses on developing the creativity, independence, and uniqueness of each child. The use of direct observation in anecdotal assessment also provides opportunities for educators to better understand the individual needs and interests of children. By analyzing children's activity anecdotes, educators can provide more accurate responses to their individual needs and interests, allowing for the development of appropriate learning strategies that support the holistic development of children.